Clinical dimensions of hypokinetic non-dilated cardiomyopathy in terms of severity and hospital outcome - Panda, Sibaram; Sharma, Sunil K.; Panda, Mayadhar (International Journal of Research in Medical Sciences, 2022)
Background: Hypokinetic non-dilated cardiomyopathy [HNDC/DCM (ND-H)] is a recently proposed (by ESC, 2016) subtype of dilated cardiomyopathy (DCM), which is characterized by the absence of left ventricular (LV) dilatation despite of global LV systolic dysfunction. Knowledge regarding clinical severity and outcomes of patients with DCM (ND-H) is very limited. Objective of the study was to evaluate clinical severity and hospital outcome of patients with HNDC [DCM (ND-H)]. Methods: Total 1248 admitted patients with primary DCM were finalized as study participants considering inclusion and exclusion criteria. The study participants were categorized into two groups depending on presence or absence of LV dilatation. 411 (32.9%) patients without any LV dilatation included in group A [HNDC/DCM (ND-H) group] and 837 (67.1%) patients with LV dilatation included in group B [DCM (D-H) group]. Data with respect to clinical, electrocardiographic, echocardiographic findings and disease outcome of patients compared statistically between the two groups. Conclusions: HNDC [DCM (ND-H)] is a subclinical subtype, which represents 1/3rd population of DCM. Apart from absence of cardiomegaly, typical clinical signs, electrocardiographic abnormalities, from which we can suspect heart disease, were less prevalent in patients with DCM (ND-H). Therefore, patient most often miss the diagnosis till the advance stage. Non cardiac co-morbidities along with late diagnosis can be important contributing factors for adverse clinical outcomes in patients with DCM (ND-H) comparable to the DCM (D-H) counterpart.